PERBUDAKAN MODERN (MODERN SLAVERY) (ANALISIS SEJARAH DAN PENDIDIKAN) - Muhamad Tisna Nugraha (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2015)
Slavery is a form of employing a person and putting him/her under the control of another. Such control includes restriction, use of physical energy or perhaps even his/her mind without compensation such as a decent wage or other forms of respect. Slavery does not always appear in the form of physical pressure, but it can also be in the psychological form by demanding someone to do something for the interests of another due to power, indebtedness or religious texts. Traces of slavery in the course of human history, in fact, have been found since ancient times in Mesopotamia, Egypt, Europe or Arabia. It can also be found in the practice of Abrahamic religions such as Judaism, Christianity, and Islam. So it is undeniable that slavery is not a novelty and will always appear in the historical journey of human life with a variety of forms. The Islam religion brought by Prophet Muhammad (pbuh), as one of the Abrahamic religions is basically against slavery. It can be seen from the history and from its teachings against the practice of slavery. Islam also strongly advocates respect for the rights of a slave especially for labor. Therefore, all forms and manifestation of slavery, including in the field of education must be resolved immediately.